Therapeutic Efficacy of Clindamycin in Dogs NaturallyInfected with Babesia gibsoni - Gonmei, Chamniugongliu; sarma, kalyan; Roychoudhury, Parimal; Eregowda, Chethan Gollahalli; Tolenkhomba, Thingujam Chaa; Prasad, Hridayesh; Rajesh, Justus Babykutty; Singh, Ningthoujam Suraj (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
As there are no anti-babesial therapies to eliminate the parasite from the animal’s body to date, pets that survive acute infections are at risk for recurring clinical disease and serve as reservoir hosts. This study was undertaken to evaluate the therapeutic efficacy of clindamycin for the treatment of dogs naturally infected with Babesia gibsoni. Dogs of various breeds and age groups of either sex diagnosed with Babesia gibsoni infection by blood smear examination and confirmed by PCR were selected for the study. Positive cases (n=12) were divided into two equal groups to evaluate the therapeutic efficacy of two drugs, viz., Gr. A (Diminazene aceturate @ 3.5 mg/kg b.wt., i/m once) and Gr. B (Clindamycin @ 11 mg/kg b.wt., i/v q24 h for 10 days) both with supportive treatment. All animals showed clinical cure with improvement in appetite and physical activity by day seven post-treatment with gradual increase in haematological parameters including platelet count and serum biochemistry values, and antioxidant level, i.e., TA, GSH and SOD, and reduced oxidative stress, i.e., LPO, in both the treated groups till day 21 post-treatment. The finding suggests that clindamycin along with supportive therapy might be useful for the treatment of dogs naturally infected with B. gibsoni infection as a substitute of Diminazene aceturate.